Hubungan Pengetahuan dan Sikap Pasangan Usia Subur (PUS) dalam Pemilihan Alat Kontrasepsi Implant Di Wilayah Kerja Puskesmas Astambul Kabupaten Banjar Tahun 2024 - Kartika Dwi Agustina (Jurnal Kesehatan Indonesia, 2025)
Family planning helps married couples delay or avoid pregnancy to manage birth spacing. In 2023, the Astambul Health Center recorded 4,991 active family planning participants. However, implant contraceptive users accounted for only 51.2%, far below the 80% annual target. This study aims to analyze the relationship between knowledge and attitudes of couples of reproductive age and their selection of implant contraceptives in the Astambul Health Center area in 2024. This quantitative analytic research used a case-control study design. The sample included 198 respondents 99 implant contraceptive users (case group) and 99 non-users (control group) selected through simple random sampling. The study was conducted from July to December 2024. The dependent variable was the selection of implant contraceptives, and the independent variables were knowledge and attitudes. Data were collected using a structured questionnaire and analyzed with the Chi-Square test. The Chi-Square test showed a significant relationship between knowledge and the selection of implant contraceptives (p = 0.000; p < 0.05), as well as between attitudes and the selection of implant contraceptives (p = 0.000; p < 0.05). Knowledge and attitudes of couples of reproductive age are significantly associated with their decision to use implant contraceptives in the Astambul Health Center working area.